Radiocarbon Ages from Beaches on Joinville Island, Antarctic Peninsula - Simms, Alexander (IEDA: US Antarctic Program Data Center, 2022)
This dataset consists of the location, elevation, and age of samples obtained from Joinville Island along the Antarctic Peninsula